Ubiquitin and Not Only Unfolded Domains Drives Toscana Virus Non-Structural NSs Protein Degradation - Gianni Gori Savellini; Luca Bini; Assunta Gagliardi; Gabriele Anichini; Claudia Gandolfo; Shibily Prathyumnan; Maria Grazia Cusi (Viruses, 2020)
The non-structural protein NSs of the Phenuiviridae family members appears to have a role in the host immunity escape. The stability of Toscana virus (TOSV) NSs protein was tested by a cycloheximide (CHX) chase approach on cells transfected with NSs deleted versions fused to a reporter gene. The presence of intrinsically disordered regions (IDRs) both at the C- and N-terminus appeared to affect the protein stability. Indeed, the NSsΔC and NSsΔN proteins were more stable than the wild-type NSs counterpart. Since TOSV NSs exerts its inhibitory function by triggering RIG-I for proteasomal degradation, the interaction of the ubiquitin system and TOSV NSs was further examined. Chase experiments with CHX and the proteasome inhibitor MG-132 demonstrated the involvement of the ubiquitin-proteasome system in controlling NSs protein amount expressed in the cells. The analysis of TOSV NSs by mass spectrometry allowed the direct identification of K104, K109, K154, K180, K244, K294, and K298 residues targeted for ubiquitination. Analysis of NSs K-mutants confirmed the presence and the important role of lysine residues located in the central and the C-terminal parts of the protein in controlling the NSs cellular level. Therefore, we directly demonstrated a new cellular pathway involved in controlling TOSV NSs fate and activity, and this opens the way to new investigations among more pathogenic viruses of the Phenuiviridae family.